Automatic Character Assignation - LYNCH, GERARD; VOGEL, CARL (Springer, 2007)
This article outlines a simple method for parsing an ASCII-format dra- matic work from the Project Gutenberg Corpus into separate characters. The motivation for the program is a upcoming study in computational stylistics and characterization in drama. Various previous approaches involving interactive media are examined and the parser is evaluated by comparing the output to data annotated by hand and parsed automat- ically by the Opensourceshakespeare.org project parser. An acceptable level of accuracy is achieved, and it is identified how to improve accuracy to extremely high levels.
PUBLISHED
Keywords: Computer Science